Penerapan Catalytic Converter Berbahan Kuningan, Nikel, Dan Karbon Aktif Sebagai Upaya Penurunan Emisi Gas Buang Co Dan Hc Pada Mesin Bensin - Pramudita Putri Audina Winasti; Moch. Aziz Kurniawan; Raka Pratindy; Aat Eska Fahmadi; Riza Phahlevi Marwanto (Jurnal Ragam Pengabdian, 2026)
Exhaust emissions from motor vehicles are a leading source of air pollution in urban areas, particularly carbon monoxide (CO) and hydrocarbon (HC) produced by incomplete combustion. This study examines the performance of a catalytic converter constructed from a composite combination of brass, nickel, and activated carbon materials in mitigating CO and HC emission levels produced by a Suzuki Carry Pick Up gasoline-powered vehicle. An experimental approach was used, measuring exhaust emissions before and after catalytic converter installation at five engine speeds—idle, 1500, 2000, 2500, and 3000 rpm—with three repetitions per condition. Measurements were taken using a calibrated gas analyzer at the Cilincing Vehicle Testing Unit, Jakarta. Results demonstrated that the catalytic converter reduced average CO emissions by 48.29%, from 0.343% to 0.177%, and HC emissions by 16.67%, from 152.4 ppm to 126.7 ppm. Higher engine speeds generally yielded lower emission levels, consistent with improved combustion efficiency as the air-fuel ratio (AFR) approached the stoichiometric value of 14.7:1. A temporary increase in emissions at 2500 rpm was attributed to valve overlap and combustion chamber pressure dynamics at mid-range speeds. These results confirm that brass and nickel as catalysts combined with activated carbon as an adsorbent represent an effective and economically accessible alternative to precious metals in catalytic converter fabrication.